Hemodynamic analysis for stenosis microfluidic model of thrombosis with refined computational fluid dynamics simulation - Yunduo Charles Zhao (Nature Portfolio, 2021)
Abstract Disturbed blood flow has been increasingly recognized for its critical role in platelet aggregation and thrombosis. Microfluidics with hump shaped contractions have been developed to mimic microvascular stenosis and recapitulate the prothrombotic effect of flow disturbance. However the physical determinants of microfluidic hemodynamics are not completely defined. Here, we report a refined computational fluid dynamics (CFD) simulation approach to map the shear rate (γ) and wall shear stress (τ) distribution in the stenotic region at high accuracy. Using ultra-fine meshing with sensitivity verification, our CFD results show that the stenosis level (S) is dominant over the bulk shear rate (γ 0) and contraction angle (α) in determining γ and τ distribution at stenosis. In contrast, α plays a significant role in governing the shear rate gradient (γ ′) distribution while it exhibits subtle effects on the peak γ. To investigate the viscosity effect, we employ a Generalized Power-Law model to simulate blood flow as a non-Newtonian fluid, showing negligible difference in the γ distribution when compared with Newtonian simulation with water medium. Together, our refined CFD method represents a comprehensive approach to examine microfluidic hemodynamics in three dimensions and guide microfabrication designs. Combining this with hematological experiments promises to advance understandings of the rheological effect in thrombosis and platelet mechanobiology.